An Innovative Application of Diagonal Ridge Elements of Classical Suzhou-style Buildings to Furniture Design Based on Kansei Engineering and Shape Grammar - Yin Jing; Yongsheng Cheng; Sheng Yu; Jiaye Lin (BioResources, 2024)
This paper proposes a furniture design method combining Kansei engineering (KE) and shape grammar (SG), to explore how the diagonal ridge elements of classical Suzhou-style buildings can be applied to furniture design and to explain how the styling elements match the cultural imagery in furniture products. Suzhou-style armchairs and cultural elements of diagonal ridges were collected, the most suitable armchairs were selected for incorporating such elements, and their shapes were deconstructed along with characteristic interpretations. A factor bank of diagonal ridge elements was constructed, first through Kansei word selection and evaluation experiments, and then through factor analysis which determined the main cultural elements of the design. The shape grammar theory was applied to design and innovate the selected armchair samples, achieving three design solutions. The solutions were then comprehensively evaluated, and the optimal one was used for the final physical product. The results of the study showed that users had clear subjective feelings about the design incorporating diagonal ridge elements, with their Kansei on three aspects: aesthetic style, decorative complexity, and structural balance. The approach used in this work blends furniture products with cultural imagery on diagonal ridges, providing a feasible methodological reference and an empirical case for cultural sustainability through furniture design.